Cobalt-containing hexagonal mesoporous molecular sieves (Co-HMS): Synthesis, characterization and catalytic activity in the oxidation reaction of ethylbenzene - Bhoware, Shrikant S.; Shylesh, S.; Kamble, K. R.; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2006)
Cobalt-containing hexagonal mesoporous materials (Co-HMS and Co/HMS) with different cobalt content were synthesized for the first time by direct hydrothermal and post-synthesis (grafting) method. The materials were characterized in detail by X-ray diffraction, BET surface area, N-2 sorption isotherms, SEM, TEM, UV-vis and XPS techniques. Powder X-ray diffraction pattern, N2 adsorption-desorption analysis and TEM analysis show the presence of hexagonal mesoporous structure, having Type W isotherms and reveals the typical wormhole-like morphology. Spectroscopic techniques like UV-vis and XPS reveal cobalt in +2 oxidation state and tetrahedrally coordinated. Liquid phase oxidation of ethylbenzene using TBHP (70 wt%) as an oxidant shows that the catalysts are highly active, under solvent free conditions as well as under lower cobalt concentrations. Leaching studies performed by hot filtration experiments show that the cobalt catalysts prepared by hydrothermal methods are stable, while the grafted catalysts show the leaching of cobalt under the reaction conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Co-HMS; ethylbenzene; HMS; hydrothermal; Oxidation

Chromium-containing small pore mesoporous silicas: synthesis, characterization and catalytic behavior in the liquid phase oxidation of cyclohexane - Shylesh, S.; Samuel, Prinson P.; Singh, A. P. (Applied Catalysis A-General, 2007)
Organic-inorganic hybrid mesoporous silica materials containing chromium and various organo trialkoxysilanes (chloropropyl, vinyl, methyl) were prepared by the co-condensation method, in the presence of cetyl trimethyl ammonium surfactants. The hybrid material, containing chromium, retains one X-ray diffractogram (XRD) peak up to a molar ratio of 1: 1 between tetra ethyl orthosilicate (TEOS) and organosilane in the synthesis gel. Small pore mesoporous chromium-silica samples can be prepared from the large pore hybrid mesoporous chromium samples by calcination. By this method, the pore size of the material can be tailored into the supermicroporous region, without changing the chain length of the surfactant used in the assembly process, as judged from the XRD and N-2 sorption isotherms. The shrinkage in pore size is dependent on the nature and percentage of the organic pendant groups, such that the chloro propyl and vinyl pendant mesoporous material show more pore size shrinkage than the smaller methyl pendant units. Because of the tailorable pore size and with better textural characteristics, the chromium samples show better catalytic activity in the aerial oxidation reaction of cyclohexane than the conventional chromium-containing mesoporous material, like Cr-MCM-41, under a solvent free system. Among the porous chromium catalysts, the samples prepared using chloro propyl silane show higher cyclohexane conversion and cyclohexanone selectivity and behave as a true heterogeneous catalyst. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: chromium; Cyclohexane; Oxidation; small pore silicas

Catalytic aerobic oxidation of cyclohexane and ethyl benzene over chromium-containing mesoporous organosilicas - Singh, A. P.; Torita, N.; Shylesh, S.; Iwasa, N.; Arai, M. (Catalysis Letters, 2009)
Chromium-containing ethane-bridged hybrid periodic mesoporous organosilicas (Cr-PMO) were synthesized using 1,2-bis(triethoxysilyl) ethane (BTEE) and tetraethyl orthosilicate (TEOS) as silica sources and alkyltrimethyl ammonium salts as surfactants by two different synthesis routes. PXRD and N(2) adsorption-desorption analysis shows that the original structure of the materials is maintained after chromium substitution while spectroscopic study proves the incorporation of chromium in the frame wall positions and show the existence of Cr(2)O(3) species in the mixed silica source (BTEE-TEOS) synthesized chromium samples. The catalytic activity of the newly developed chromium samples was evaluated in the liquid phase oxidation of cyclohexane and ethylbenzene using air as an oxidant. Further, the Cr-PMO samples exhibited better cyclohexane conversion and cyclohexanone selectivity than the conventional Cr-MCM-41 and other metal-containing MCM-41 samples. The exceptional activity of the new chromium-containing molecular sieves is attributed to the hydrophobicity of the materials and to the complementary structural features that facilitates the accessibility of substrate to the active framework chromium sites.
Keywords: Cr-MCM-41; Cyclohexane; Ethyl benzene; Organosilicas; Oxidation

Catalytic meerwein-ponndorf-verley reductions over mesoporous silica supports: rational design of hydrophobic mesoporous silica for enhanced stability of aluminum doped mesoporous catalysts - Shylesh, S.; Kapoor, Mahendra P.; Juneja, Lekh R.; Samuel, Prinson R.; Srilakshmi, Ch; Singh, A. R. (Journal of Molecular Catalysis A-Chemical, 2009)
A series of aluminum isopropoxide-grafted mesoporous organosilica having ethane (-CH(2)-CH(2)-) and ethene (-CH=CH-) groups in the frame wall positions (ethane-silica, ethene-silica) as well as mesoporous silicas (MCM-41, MCM-48. SBA-15) through siloxide linkages were fabricated. The samples were used as catalysts in the Meerwein-Ponndorf-Verley reduction of ketones and aldehydes of different nature and size using secondary alcohols as the hydrogen transfer agents. Aluminum isopropoxide supported mesoporous silica samples show higher catalytic conversion and among them, the one-dimensionally channel oriented Si-MCM-41 supported aluminum isopropoxide shows better results than the three-dimensional Si-MCM-48 and the large pore Si-SBA-15. Compared to aluminum isopropoxide-grafted mesoporous silica samples, aluminum alkoxide-grafted organosilica samples shows better catalytic activity even in the presence of 10% of water and the better stability is attributed to the presence of integrated hydrophobic organic groups in the frame wall positions. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Aluminum isopropoxide; Mesoporous silica; Organosilica; reduction